Building bridges that change state Islamic universities in Indonesia toward international standard - Tasman Hamami; Siti Nur Hidayah; Miftahus Sa’adah (International Journal of Evaluation and Research in Education (IJERE), 2021)
The learning organization is a strategic process for every university as a public service institution to improve its performance. Learning organizations have an essential role in linking past experiences to future improvements in changing State Islamic Universities in Indonesia to achieve international standards. This study aimed to describe the State Islamic University's learning organization profile in Indonesia and reveal its readiness towards international standards. This study used a survey approach, collecting data through closed questionnaires and open-ended questions involving 300 respondents consisting of lecturers and employees of the State Islamic University of Sunan Kalijaga Yogyakarta. The data analysis technique used descriptive statistics with a benchmark scale and explanations. The results showed that the average score on all learning organization variables was low, below the benchmark scale. This result was in line with lecturers and employees' perception that most of them (68%) expressed pessimism about universities' readiness to achieve international standards. In conclusion, the State Islamic University of Sunan Kalijaga has not fully become a learning organization as a bridge of change towards an international standard.